Tantangan dan Peluang dalam Implementasi Pendidikan Berbasis Teknologi di SMP Islam Andalusia Kebasen - Ali Masngud; Muh. Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The implementation of technology-based education in schools in Indonesia offers various opportunities to improve the quality of learning and access to education. However, this process also presents complex challenges, especially related to infrastructure gaps, digital literacy, and curriculum adaptation. This study aims to identify challenges and opportunities in the implementation of technology-based education in SMP Islam Andalusia Kebasen using a qualitative approach. Data were collected through semi-structured interviews, field observations, and document analysis from various sources, including teachers, students, and policy makers. The results of the study indicate that the main obstacles include limited access to technological devices, low digital competence among educators and students, and financial constraints. On the other hand, significant opportunities were found in the form of increasing learning flexibility, potential for global collaboration, and the development of more innovative teaching methods. This study concludes that to realize a successful implementation, collaborative efforts are needed between the government, schools, and the community in overcoming challenges and utilizing existing opportunities. Strategic efforts include improving technological media, digital literacy training programs, and developing policies that support the integration of technology in education. This study provides relevant insights to support the transformation of inclusive and sustainable technology-based education in Indonesia